Electric‐field‐coupled contactless ID sensor for cm‐level high‐precision positioning item‐level tagging systems. Issue 10 (1st May 2016) - Jeong, M.‐G.; Kim, J.‐H.; Bae, S.‐H.; Lee, W.‐S.
Abstract : To detect multiple identifications (IDs) for cm ‐level high‐precision positioning item‐level tagging (ILT) systems in near‐field ultra‐high‐frequency RFID applications, an electric‐field‐coupled multiple ID sensor is presented. The proposed ID sensor consists of four circular electric coupling parts, an impedance‐matching network, and an SP4T switch for position control. By switching the electric‐field‐coupled sensing parts, cm ‐level position detection of densely aggregated RFID tags for a small‐sized ILT can be achieved. The sensing distance of the proposed ID sensor is ∼7 mm and its physical size is 50 × 50 mm 2 (∼1/7 λ 0 at 920 MHz).